Computational Strategies for Predicting Excited-State Energies in Eu3+Down-Shifting Spectral Converters for Photovoltaic Devices - Aravena-Ponce, D; Aravena-Ponce, D (WILEY-V C H VERLAG GMBH, 2025)
In this work, a computational protocol has been developed to predict the ligand-based low-lying excited-state energies of Eu3+ coordination compounds with antenna ligands. A computational strategy, based on density functional theory (DFT) and time-dependent density functional theory (TD-DFT), has been developed using compounds with reliable structural and spectroscopic experimental data as a reference set. This approach aims to predict both the geometry and energy of the lowest-excited triplet state, critical factors influencing the efficiency of the antenna effect and energy transfer to the Eu3+ ion. The model not only shows the ability to replicate available experimental data at a relatively low computational cost, but also accurately predicts triplet-state energies for compounds that have not been included in the training set. This work is a first step toward the development of an affordable method for accurate predictions of the quantum yield of lanthanide-based complexes to assess their potential application as down-shifting spectral converters in solar cells.
Keywords: antenna effect; density functional theory; emission; lanthanides; time-dependent density functional theory